Continental Tectonics Inferred From High‐Resolution Imaging of the Mantle Beneath the United States, Through the Combination of USArray Data Types. (25th October 2021) - Bedle, Heather; Lou, Xiaoting; van der Lee, Suzan
Abstract: A comprehensive North American upper mantle seismic‐tomographic model, NA13, was inferred from a combination of several decades of seismic data from early North American seismic networks and USArray data. This data‐driven modeling inverted a combination of regional waveform fits, teleseismic S delay times, and point constraints on Moho depths. The joint inversion model combines the contrasting and overlapping resolving power of the different data sets, and demonstrates enhanced resolution over regional models created with a single geophysical data set. Resolution in the upper mantle is achieved on the scale of ∼100 km, although travel time delay studies suggest that anomalies in parts of the western United States are smaller. In NA13, velocities beneath the Yellowstone plume are low enough to require the presence of partial melt. NA13 also models a variety of smaller scale velocity variations beneath the Central and Eastern United States that reveal remnant velocity anomalies related to lithospheric variations in the upper mantle between Proterozoic units. Plain Language Summary: Seismic tomography has been used for decades to image the structure of the interior of the Earth. NA13 is an updated tomographic model that expands on previous models by combining multiple types of data from seismic recordings of earthquakes to allow the imaging of smaller scale features in the upper mantle beneath the United States. These methods allow NA13 to be created on a regional, continental scale, while still being able to image smaller‐scale features that are typically absent in regional models. Of interest, NA13 suggests that partial melt must exist beneath Yellowstone, and reveals anomalies beneath the Central and Eastern United States related to Mesozoic and Cenozoic tectonics. Key Points: Joint inversion that includes USArray data allows enhanced resolution of regional upper mantle velocity models NA13 reveals small scale velocity variations beneath the Central and Eastern United States Upper mantle velocity variation is on the order of ∼100 km